Design and proof-of-concept of an advanced protective system for the dissipation of tangential impact energy in helmets, based on non-Newtonian fluids. (16th March 2023) - La Fauci, Giuseppe; Parisi, Mariafederica; Nanni, Alessandro; Crosetta, Lorenzo; Pugno, Nicola M; Colonna, Martino
Abstract: We have designed and tested a device based on non-Newtonian fluids for the attenuation of tangential impacts energy in helmets. A shear thickening fluid based on borurated silicones has given the best results in terms of impact energy attenuation in a system that selectively mimics tangential impacts and for this reason it has been used to fill the chamber of a pad, prepared by additive manufacturing, for impact energy dissipation. The pad is composed of a case containing the fluid in which is immersed a rigid pin that is free to move in all direction and therefore is able to absorb energy during its movement inside the fluid. A motorcycle helmet, already composed of two concentrical expanded polystyrene (EPS) liners, has been implemented with seven pads between the two EPS layers. The two layers have only been connected by means of the dissipating pad and are free to rotate and to dissipate energy during the rotation. The results of oblique impacts according to ECE 22.06 with three impact positions, shows a reduction of the brain injury criterion of 14% for the helmet with the pads, compared to the standard helmet, with values well below the threshold imposed by the norm. On the contrary, the maximum of the peak rotational acceleration show a 3% increase. Nevertheless, the rotational acceleration versus time curves indicates that in all three orientations the time of the maximum is shifted towards longer times for the helmets with the pads, indicating that the pads retard the acceleration of the head due to the efficient rotation of the two EPS parts connected by the pads. The described system could be implemented with minimal modifications in existing protective sport and motorcycle helmets.